Cultivating Qur'anic Character Through The Sekolah Sisan Ngaji Program In Paud Institutions (Implementation Of Blora Regency Government Program) - Irchamni, Achmad; Kristiyuana, Kristiyuana; Kaswari, Haji (JURNAL PEDAGOGY, 2025)
Character education is an effort to realize values that are considered lost today. Good character will form a good soul. Quality character needs to be fostered and formed from an early age (golden age), because this period has been proven to be very decisive in determining a child's ability to develop their potential. This research is field research using a qualitative descriptive approach, which is research that seeks to describe systematically, factually and accurately the facts and characteristics of a particular population. Based on the results of research on the cultivation of Qur'anic character in early childhood at BA Aisyiyah Ngawen, the research findings include: 1) Methods of cultivating Qur'anic character in early childhood. The cultivation of Qur'anic character in early childhood at BA Aisyiyah Ngawen consists of habituation of Dhuha Prayer, Qur'an Recitation, and reading Stories of Prophets and Messengers. 2) Supporting factors and inhibiting factors for cultivating Qur'anic character in early childhood at BA Aisyiyah Ngawen, namely supporting factors include maturity and good environmental factors. And the inhibiting factors are nutritional or dietary intake factors and poor environmental factors.